Background: Genital herpes is the most common genital tract infection that results into high rate of morbidity and mortality of neonates on vertical transfer and also of females. Objective: To evaluate the management policies/techniques for HSV infection - Hina Pirzada, Shagufta Parveen, Sadia Habib, Wajiha Mehwish, Rukhsana Saboor, Tayyaba Rasheed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Genital herpes is the most common genital tract infection that results into high rate of morbidity and mortality of neonates on vertical transfer and also of females. Objective: To evaluate the management policies/techniques for HSV infection during gestation period. Study Design: Retrospective study Place and Duration of Study: Department of Obstetrics & Gynaecology, AJK Medical College Muzaffarabad Azad Kashmir from 1st January 2021 to 30th June 2021. Methodology: Sixty females were enrolled within the age of 21-39 years who were pregnant and having complete clinical symptoms of sore-vesicle clusters and minimal ulceration. 4cc blood was withdrawn with division into 2cc whole blood for PCR testing and 2 cc into serum for viral antigen detection through ELISA based kits against HSV 1 and HSV 2 antigens. Results: The mean age of 31.0± 4.2 years and majority of the women 48.3% were within the age of 34-39 years. The management therapy was found efficient in women suffering from herpes simplex virus 91.6% reduction found on polymerase chain reaction (PCR) reporting. Within the HSV 1 and HSV 2 pregnant women spontaneous delivery was observed in 24 (40%) women while rest 36 (60%) underwent cesarean delivery Conclusion: Genital herpes infection can be managed and treated by using antiviral medications and through cesarean deliveries in majority of the participants. Keywords: Genital herpes, Cesarean, Transmission, Neonates